2008
DOI: 10.1121/1.2963048
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the R reflector and sediment interface reflection at the Shallow Water ’06 Central Site

Abstract: Acoustic bottom-interacting measurements from the Shallow Water ’06 experiment experiment (frequency range 1–20kHz) are presented. These are co-located with coring and stratigraphic studies showing a thin (∼20cm) higher sound speed layer overlaying a thicker (∼20m) lower sound speed layer ending at a high-impedance reflector (R reflector). Reflections from the R reflector and analysis of the bottom reflection coefficient magnitude for the upper two sediment layers confirm both these features. Geoacoustic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 17 publications
2
30
0
2
Order By: Relevance
“…Choi et al 7 analyzed close range high frequency (1-20 kHz) bottom loss data from the same site, and inferred the attenuation from a very thin surficial sediment layer from inversions of the measured loss. They found that a frequency dependence of 0.2͑f / f ref ͒…”
Section: Resultsmentioning
confidence: 99%
“…Choi et al 7 analyzed close range high frequency (1-20 kHz) bottom loss data from the same site, and inferred the attenuation from a very thin surficial sediment layer from inversions of the measured loss. They found that a frequency dependence of 0.2͑f / f ref ͒…”
Section: Resultsmentioning
confidence: 99%
“…• Waveform and bottom loss matching (Choi et al 2008) • Matched field inversion • Matched field inversion (Huang et al, 2008) • Wavenumber extraction inversion (Ballard et al, 2010).…”
Section: Work Completedmentioning
confidence: 99%
“…및 음속, 감쇄계수 역산, [1] 다층 구조 퇴적층에서 수 신된 반사 손실을 이용한 퇴적층의 두께 및 지음향 인자 역산, [2] 해양에 존재하는 주변 소음의 수신 위 상 정보를 이용한 하부 퇴적층 구조 역산 [3] 에서 제 공받은 평균입도자료를 이용하여 계산되었다.…”
unclassified